Fibroepithelial Lesions in the Breast of Adolescent Females: A Clinicopathological Study of 54 Cases. Issue 2 (4th November 2016) - Ross, Dara S.; Giri, Dilip D.; Akram, Muzaffar M.; Catalano, Jeffrey P.; Olcese, Cristina; Van Zee, Kimberly J.; Brogi, Edi
Abstract: Fibroepithelial lesions (FELs) are the most frequent breast tumors in adolescent females. The pubertal hormonal surge could impact the growth and microscopic appearance of FELs in this age group. In this study, we evaluate the morphology and clinical behavior of FELs in adolescents. We searched the 1992–2012 pathology data base for FELs in females 18 years old or younger (F ≤18 years). Seven FELs from 1975 to 1983 were also included. Three pathologists reviewed all available material. Patient (pt) characteristics and follow‐up information were obtained from electronic medical records. Forty‐eight F ≤18 years had 54 FELs with available slides. Thirty (67%) pts were Caucasian, 12 (27%) African‐American, two (4%) Hispanic, one (2%) Asian; three were of unknown race/ethnicity. Median age at diagnosis was 16 years. Median age at menarche was 12 years; most (96%) FELs occurred after menarche (median interval 48 months). All patients underwent lumpectomy; one required subsequent mastectomy. The FELs were 34 fibroadenomas (FAs) (11 usual, 23 juvenile), and 20 phyllodes tumors (PTs) (16 benign, one borderline and three malignant). Eight (35%) juvenile FAs showed slight intratumoral heterogeneity. The mean mitotic rate was 1.3 mitoses/10 high‐power fields (HPFs) (range, 0–6) in usual FAs, 1.8/10 HPFs in juvenile FAs, 3.1/10 HPFs in benign PTs, 10/10 HPFs in the borderline PT and 17/10 HPFs in malignant PTs. The mean follow‐up for 29 pts with 33 FELs was 44 months. Two (10%) PTs recurred locally (a benign PT at 18 months, and a borderline PT at 11 months). Both recurrent PTs had microscopic margins <1 mm. Mitotic activity in FAs from adolescents can be substantial and this finding should be interpreted cautiously. Awareness of the morphologic features of FELs in adolescents is important to avoid overdiagnosis of PTs, which can lead to additional unnecessary and potentially disfiguring surgery.